26 Impact of Severity Of Perinatal Asphyxia on Peripheral Oxygenation and Perfusion in Neonates. (October 2012) - Pichler, G; Tax, N; Binder, C; Pocivalnik, M; Pichler-Stachl, E; Müller, W; Urlesberger, B
Abstract : Objective: The aim was to investigate the influence of perinatal asphyxia on peripheral oxygenation and perfusion in neonates in a prospective observational study. Methods: Neonates with over 34 weeks gestational age and birth weight >2000g without sepsis or connatal malformations were included. Neonates with an umbilical artery pH of (UapH) ≤7.15 and 5 minute APGAR score ≤6 were investigated. Neonates with an UapH ≥7.15, and 5 minute APGAR score ≥7 served as control group. Peripheral muscle near infrared spectroscopy (NIRS) measurement in combination with venous occlusion was performed once in the first 48 hours after birth. Tissue oxygenation index (TOI), mixed venous oxygen saturation (SvO2), fractional oxygen extraction (FOE), haemoglobin flow (Hbflow), oxygen delivery (DO2) and oxygen consumption (VO2) were assessed. Furthermore arterial oxygen saturation, heart rate, blood pressure und temperatures were measured. UapH was correlated to NIRS parameters. Results: Eight asphyxiated neonates were included. In the asphyxiated group significant correlations between UapH and DO2 (r=0.78), VO2 (r=0.80) and FOE (r=–0.75) were found. The asphyxiated neonates were compared to 30 neonates in the control group. TOI (67.7±5.5%) and DO2 (29.0±14.2 µmol/100/l/min) were significantly lower in asphyxiated neonates compared to the controls (TOI 71.8±4.9%, DO2 43.9±16.9 µmol/100/l/min), FOE was significantly higher (0.33±0.05) compared to the controls (0.28±0.06). No correlation of UapH with NIRS parameters was observed in the control group. Conclusion: Peripheral oxygenation and perfusion measured with NIRS is compromised in neonates with perinatal asphyxia with worsening of parameters with severity of asphyxia.